How long-term housing demand is being addressed in refugee resettlement - Depperschmidt, Olivia (My University, 2025)
Refugees are individuals who have fled their home country due to a well-founded fear of persecution and are resettled in a new country. The United States provides all refugee with social services, including assistance in applying for food and cash assistance, understanding public transportation, applying for jobs and placement in housing. But how refugees are placed in housing is unknown. To fill this gap, I conducted a case study of the Twin Cities to explore the process through which refugee housing need is addressed in this area. The Twin Cities have a long and successful history of resettlement of refugees. Refugees thrive in the area because of resettlement agencies, stakeholders and ethnic communities, comparatively low unemployment rate, and an average median income 109% higher than Minnesota. Refugees are successfully placed in housing because resettlement agencies work together to tackle problems and share housing resources. Additionally, resettlement agencies prioritize their relationship with landlords. The presence of ethnic communities also help with placement of refugees in housing. Finally, elimination of single-family zoning has resulted in increased multi-family high-density development, thus creating additional housing options for refugees. The results of my research provide refugee resettlement agencies, cities, and city planners with the best practices and policies for placing refugees in housing.
Keywords: Refugee; Refugee resettlement; Housing; Twin Cities